Physicochemical Properties and In Vitro Cytotoxicity Studies of Chitosan as a Potential Carrier for Dicer-Substrate siRNA. (12th September 2013) - Abdul Ghafoor Raja, Maria; Katas, Haliza; Abd Hamid, Zariyantey; Razali, Nur Atiqah
Abstract : Recently, Dicer-substrate small interfering RNA (DsiRNA) has gained attention owing to its greater potency over small interfering RNA (siRNA). However, the use of DsiRNA is restricted by its rapid degradation in vitro . To address this issue, chitosan nanoparticulate deliver yplatform for the Dicer-substrate siRNA (DsiRNA) was developed and characterized. Nanoparticles were prepared by simple complexation and ionic gelation methods. The mean particle size of DsiRNA-adsorbed chitosan nanospheres (DsiRNA-CS NPs) prepared by the ionic gelation method ranged from 225 to 335 nm, while simple complexation yielded DsiRNA-chitosan complexes (DsiRNA-CS complexes) ranging from 270 to 730 nm. The zeta potential of both types of nanoparticles ranged from +40 to +65 mV. TEM and AFM micrographs revealed spherical and irregular morphology of DsiRNA-CS NPs and DsiRNA-CS complexes. ATR-FTIR spectroscopy confirmed the presence of DsiRNA in the CS NPs/complexes. Both types of nanoparticles exhibited sustained release and high binding and encapsulation (100%) efficiency of DsiRNA. DsiRNA-CS NPs/complexes showed low, concentration-dependent cytotoxicity in vitro . DsiRNA-CS NPs showed better stability than the complexes when stored at 4 and 25°C. Thus, it is anticipated that CS NPs are promising vectors for DsiRNA delivery due to their stability, safety, and cost-effectiveness.